Environmental Law Handbook - Sarah Kolda (Issues in Science and Technology Librarianship)
This article reviews the book Environmental Law Handbook. 15th ed. Rockville, MD : Government Institutes, 1999. 700 p. hardcover $89.00 (ISBN 0-86587-650-7), edited by Thomas F.P. Sullivan.